Bioassay-guided isolation and POM analyses of a new immunomodulatory polyphenolic constituent from Callistemon viridiflorus. Issue 10 (18th May 2016) - Abdelhady, Mohamed I.S.; Kamal, Amel M.; Rauf, Abdur; Mubarak, Mohammad S.; Hadda, Taibi Ben
Abstract : Chromatographic separation of 80% EtOH extract of Callistemon viridiflorus leaves led to the isolation of six known constituents (1 –6 ) along with a new polyphenolic compound7 identified as apigenin 4′- O -β-d -glucopyranosyl-(1″′ → 4″)- O -β-d -glucopyranoside. The ethanolic extract of C. viridiflorus leaves and isolated compounds were evaluated for in vitro immunomodulatory activity by means of RAW 264.7 macrophages proliferation (MTT) assay. Ethanolic extract of leaves and compounds1, 3, 4, 6 and7 caused a significant increase in macrophage proliferation; these findings may suggest that this medicinal plant could be utilised as an excellent source of compounds for immunomodulatory activity. Abstract :